2022
DOI: 10.35772/ghmo.2022.01005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice for cervical cancer among female primary school teachers in Phnom Penh, Cambodia: A cross-sectional phone-based survey

Abstract: Cervical cancer is a cancer with evidence-based and cost-effective preventive measures; Human Papilloma Virus (HPV) vaccination for school girls and cancer screening for women. In Cambodia, cervical cancer accounts for an estimated 11.4% and 10.4% of women's cancer and deaths in 2020, respectively. This study aimed to identify the knowledge of cervical cancer, its information sources, and the experiences of cervical cancer screening among female primary school teachers, who are key influencers of HPV vaccinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Similar findings were also found in the study conducted among female secondary school teachers in Enugu, Nigeria, which showed that healthcare workers (37.2%), mass media (30.2%), and friends (17.6%) as a medium to get information about cervical cancer (Enebe et al,2021). But the contrast was found in the study conducted by Soeung et al( 2022 ) in Cambodia which reported that the most common sources of information were relatives, friends, and colleagues, followed by doctors, television, and the internet.…”
Section: Variablessupporting
confidence: 81%
“…Similar findings were also found in the study conducted among female secondary school teachers in Enugu, Nigeria, which showed that healthcare workers (37.2%), mass media (30.2%), and friends (17.6%) as a medium to get information about cervical cancer (Enebe et al,2021). But the contrast was found in the study conducted by Soeung et al( 2022 ) in Cambodia which reported that the most common sources of information were relatives, friends, and colleagues, followed by doctors, television, and the internet.…”
Section: Variablessupporting
confidence: 81%
“…The exact number of women affected with the cancer and their clinical features, including stage at diagnosis, remain unknown due to a lack of cancer registration system. Previous studies on cervical cancer in Cambodia are limited to those on cancer awareness and the prevalence of HPV and cervical dysplasia (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%